2017
DOI: 10.1186/s13007-017-0210-6
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of highly homologous Nicotiana benthamiana ubiquitin E2 gene family members in plant immunity through an improved virus-induced gene silencing approach

Abstract: BackgroundVirus-induced gene silencing (VIGS) has been used in many plant species as an attractive post transcriptional gene silencing (PTGS) method for studying gene function either individually or at large-scale in a high-throughput manner. However, the specificity and efficiency for knocking down members of a highly homologous gene family have remained to date a significant challenge in VIGS due to silencing of off-targets.ResultsHere we present an improved method for the selection and evaluation of gene fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…This study suggests that Fni3/Sl-Ubc13-2 and Suv positively regulate plant immunity [128]. By knocking down the Group III E2 genes in Nicotiana benthamiana via VIGS (gene silencing), it is found that these genes are necessary for plant development, immunity-associated ROS production, and suppression of immunity-associated PCD (programmed cell death) by AvrPtoB [134,135]. Besides, knocking down the expression of TaU4 gene which encodes a ubiquitin-conjugating enzyme 4 in Triticum aestivum by VIGS can slow down the development of disease symptoms and reduce Septoria sporulation (Mycosphaerella graminicola, commonly known as Septoria), indicating that TaU4 is a negative regulator for defense against the phytopathogen Septoria in wheat [123].…”
Section: Plant Immune Responsesmentioning
confidence: 81%
“…This study suggests that Fni3/Sl-Ubc13-2 and Suv positively regulate plant immunity [128]. By knocking down the Group III E2 genes in Nicotiana benthamiana via VIGS (gene silencing), it is found that these genes are necessary for plant development, immunity-associated ROS production, and suppression of immunity-associated PCD (programmed cell death) by AvrPtoB [134,135]. Besides, knocking down the expression of TaU4 gene which encodes a ubiquitin-conjugating enzyme 4 in Triticum aestivum by VIGS can slow down the development of disease symptoms and reduce Septoria sporulation (Mycosphaerella graminicola, commonly known as Septoria), indicating that TaU4 is a negative regulator for defense against the phytopathogen Septoria in wheat [123].…”
Section: Plant Immune Responsesmentioning
confidence: 81%
“…We also tested ZAR1-dependence of these effector-independent cell death phenotypes by subjecting N. benthamiana plants to virus-induced gene silencing (VIGS) [3840] two weeks prior to transformation and induction of ZED1 expression. Although the HR-mediated cell death induced by ZED1 ‘DT’ , ZED1 V212T and HopZ1a/ZED1 wt was unaffected in plants experiencing silencing of the negative control GUS gene (Fig 7A, left), the HR induced by all of these transformations was completely abolished in plants that received a ZAR1 silencing construct (Fig 7A, right).…”
Section: Resultsmentioning
confidence: 99%
“…Transgene expression was induced by spraying whole leaves with 20 μM dexamethasone in water with 0.01% surfactant Silwet-L77 (8 - 24h following infiltrations). Gene silencing was performed as described previously [3840], using Agrobacterium strains generously provided by Maël Baudin and Jennifer D. Lewis (University of California, Berkeley).…”
Section: Methodsmentioning
confidence: 99%
“…Ubiquitination as a major post-translational protein modification in eukaryotic cells typically entails a stepwise enzymatic cascade that is catalyzed by three different classes of enzymes, the ubiquitin-activating enzyme (E1), the ubiquitin-conjugating enzyme (E2), and the ubiquitin ligase (E3) ( Zhou and Zeng, 2017 ). During the ubiquitination process, the E2∼ubiquitin intermediate cooperates with an E3 to transfer ubiquitin to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The group III E2 enzymes were found to be essential for plant PTI and for the suppression of host immunity by the ubiquitin ligase activity of a Pseudomonas syringae pv. tomato (Pst) effector, AvrPtoB ( Zhou et al, 2017 ; Zhou and Zeng, 2017 ). Additionally, functional redundancy among group III members was revealed for their role in PTI and in AvrPtoB-mediated suppression of plant immunity.…”
Section: Introductionmentioning
confidence: 99%